Preface - Herawan, Tutut (Journal of Information Systems Research and Practice, 2024)
The Volume 2 Issue 3 of JISRP has been available online since 6th June 2024 for the regular issue of September 2024. The issue has been available online for accepted papers (uncorrected proofs).